Hepatic Infiltrates in Operational Tolerant Patients After Liver Transplantation Show Enrichment of Regulatory T Cells Before Proinflammatory Genes Are Downregulated. Issue 4 (18th February 2016) - Taubert, R.; Danger, R.; Londoño, M.‐C.; Christakoudi, S.; Martinez‐Picola, M.; Rimola, A.; Manns, M. P.; Sánchez‐Fueyo, A.; Jaeckel, E.
Abstract : Immunosuppression can be discontinued from selected and stable patients after liver transplantation resulting in spontaneous operational tolerance (SOT), although the underlying mechanisms remain elusive. Thus, we analyzed serial liver biopsy specimens from adult liver recipients enrolled in a prospective multicenter immunosuppression withdrawal trial that used immunophenotyping and transcriptional profiling. Liver specimens were collected before the initiation of weaning, at the time of rejection, or at 1 and 3 years after complete drug discontinuation. Unexpectedly, the tolerated grafts developed portal tract expansion with increased T cell infiltration after immunosuppression withdrawal. This was associated with transient and preferential accumulation of CD4 + FOXP3 + cells and a trend toward upregulation of immune activation and regulatory genes, without signs of rejection. At the same time, no markers of endothelial damage or activation were noted. Portal infiltrates persisted at 3 years but were characterized by decreased expression of genes associated with chronic immunological damage. Further, SOT was not associated with a progressive liver fibrosis up to 5 years. These data suggest that SOT involves several mechanisms: a long‐lasting local immune cell persistence with a transient regulatory T cells accumulation followed by a downregulation of immune‐activated genes over years. These results have important implications for designs and follow‐up of weaning trials. Abstract : This longitudinal follow‐up of liver transplant recipients with spontaneous operational tolerance after intentional and complete immunosuppression weaning suggests that operational tolerance is a long‐lasting active process, indicated by expanded portal tracts in which a transient accumulation of CD4+FOXP3+ regulatory T cells accompanies a subsequent downregulation of endothelial activation and rejection markers at three years after weaning in the absence of signs of rejection or progressive fibrosis. See Sawitzki's editorial onpage 1049 .